RESEÑA de : Bethany Aram & Bartolomé Yun-Casalilla, Global Goods and the Spanish Empire, 1492–1824. Circulation, Resistance and Diversity, Nueva York, Palgrave Macmillan, 2014, 322 pp. IS BN: 9781137324061. - Martínez Shaw, Carlos (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2015)
RESEÑA de : Bethany Aram & Bartolomé Yun-Casalilla, Global Goods and the Spanish Empire, 1492–1824. Circulation, Resistance and Diversity, Nueva York, Palgrave Macmillan, 2014, 322 pp. IS BN: 9781137324061.